Effects of western Pacific intraseasonal convection on surface air temperature anomalies over North America. (10th November 2019) - Yang, Ying; Zhu, Zhiwei; Li, Tim; Yao, Mengying
Abstract: Using the daily outgoing longwave radiation and 850‐hPa zonal wind over (10°S–30°N, 105°–150°E) during the extended boreal summer (May to October), the lifecycle of the western Pacific intraseasonal oscillation (WPISO) is divided into eight phases based on the first two principle components of multivariate empirical orthogonal function decomposition. Because of the pronounced northward propagation feature, the meridional location of the convection anomaly centre in each WPISO phase is quite different, leading to distinct surface air temperature (SAT) anomaly responses over the Northern Hemisphere, in which North America shows the most significant SAT anomalies, and the SAT anomalies vary significantly with WPISO phase. Under different WPISO phases, convection can induce different mid‐to‐high latitude Rossby wave trains emanating from East Asia to North America, resulting in different SAT anomaly patterns over North America. Four numerical experiments are conducted and demonstrate that the convection at different meridional locations in each WPISO phase could shape the pattern of the Rossby wave train and in turn lead to different SAT anomalies over North America. The results in this study are expected to provide predictability sources for the sub‐seasonal‐to‐seasonal (S2S) prediction of North American SAT anomalies. Abstract : The northward‐propagating WPISO presents convection at different meridional location in eight WPISO phases. Different convection shapes the pattern of the mid‐to‐high latitude Rossby wave trains from East Asia to North America, resulting in independent SAT anomalies over North America. Four idealized numerical experiments are conducted to support the underlying mechanism on the relationship between WPISO convection and North American SAT anomalies.